ANALISA PERMINTAAN PARKIR DI STASIUN PONCOL DAN TAWANG SEMARANG - Sutarto, Agung (Semarang State University, 2010)
Abstract: Activities in a railway station will generate trips which need parking space. This research is aimedÃÂ to analyzeÃÂ the difference demand characteristics between Poncol and Tawang stations. TheseÃÂ characteristicsÃÂ areÃÂ theÃÂ effectÃÂ ofÃÂ ticketÃÂ priceÃÂ toÃÂ tripÃÂ attraction,ÃÂ tripÃÂ attractionÃÂ model, transportation mode demand and parking space demand. The economic class and transportation of goodsÃÂ areÃÂ servedÃÂ inÃÂ Poncol.ÃÂ BussinessÃÂ andÃÂ executiveÃÂ classÃÂ isÃÂ servedÃÂ inÃÂ TawangÃÂ stastion.ÃÂ The correlationÃÂ betweenÃÂ tripÃÂ attractionÃÂ andÃÂ theÃÂ numberÃÂ ofÃÂ ticketÃÂ canÃÂ beÃÂ describedÃÂ inÃÂ theÃÂ following equationÃÂ : YtripÃÂ attractionÃÂ =ÃÂ 120,51ÃÂ +ÃÂ 1,0602 XticketÃÂ ÃÂ ÃÂ ÃÂ ÃÂ for PoncolÃÂ station,ÃÂ andÃÂ : YtripÃÂ attractionÃÂ =ÃÂ 175,21 + 1,3212 XticketÃÂ ÃÂ ÃÂ ÃÂ ÃÂ for Tawang station. Correlation betweenÃÂ trip attraction andÃÂ transportation mode can be describedÃÂ inÃÂ theÃÂ following equationÃÂ : Ytripattr = 7,3063 + 3,271 XprivateÃÂ car + 2,464 Xbecak + 2,406 Xmotor cycle + 2,448 Xpick upÃÂ ÃÂ for Poncol,ÃÂ and : Ytrip attractionÃÂ ÃÂ =ÃÂ 4,467 + 3,567 Xprivate car + 2,517 Xmotorcycle,ÃÂ for Tawang station. It can be concluded that the parking space demand for each passenger isÃÂ 1,48 m2ÃÂ in Poncol station and 7,3 m2ÃÂ in Tawang station. Trips attraction perÃÂ ticketÃÂ ÃÂ ÃÂ is 1,0602ÃÂ in Poncol stationÃÂ andÃÂ 1,3212ÃÂ inÃÂ TawangÃÂ station.ÃÂ Transportation mode whichÃÂ isÃÂ dominantlyÃÂ usedÃÂ in Poncol stationÃÂ isÃÂ ÃÂ motorcycle, whileÃÂ in Tawang stationÃÂ is private car and motorcycle. Private carÃÂ is often used because the public transport facility could not support the train passengerÃ¢â¬â¢s needs. There are variableÃÂ pick-upÃÂ vehiclesÃÂ in PoncolÃÂ because PoncolÃÂ stationÃÂ servedÃÂ passengersÃÂ andÃÂ goods. SRP which are used in Poncol station for passenger carÃÂ 65 SRP, motorcycle 282 SRP, pick-up 52 SRP, andÃÂ tricycle (becak) 64 SRP.ÃÂ ÃÂ SRP which are usedÃÂ in Tawang station for passenger car 235 SRP, motor cycle 350 SRP and tricycle (becak) 13 SRP. Keywords:ÃÂ trips attraction,ÃÂ parking demand,ÃÂ poncol station,ÃÂ tawang station . ÃÂ Abstrak: Kegiatan di stasiun kereta api akan menghasilkan perjalanan yang membutuhkanÃÂ ruang parkir. PenelitianÃÂ iniÃÂ bertujuanÃÂ untukÃÂ menganalisisÃÂ karakteristikÃÂ permintaanÃÂ perbedaanÃÂ antara stasiunÃÂ PoncolÃÂ danÃÂ Tawang. CiriÃÂ iniÃÂ pengaruhÃÂ hargaÃÂ tiketÃÂ keÃÂ atraksiÃÂ perjalanan,ÃÂ modelÃÂ tarikan perjalanan,ÃÂ kebutuhanÃÂ transportasiÃÂ modeÃÂ danÃÂ kebutuhanÃÂ ruangÃÂ parkir. KelasÃÂ ekonomiÃÂ dan transportasiÃÂ barangÃÂ disajikanÃÂ diÃÂ Poncol.BisnisÃÂ danÃÂ kelasÃÂ eksekutifÃÂ disajikanÃÂ diÃÂ Tawang stastion. KorelasiÃÂ antaraÃÂ dayaÃÂ tarikÃÂ perjalananÃÂ danÃÂ jumlahÃÂ tiketÃÂ dapatÃÂ digambarkanÃÂ dalam persamaanÃÂ berikut: YtripÃÂ atraksi =ÃÂ 120,51ÃÂ +ÃÂ 1,0602 XticketÃÂ untukÃÂ stasiun Poncol, dan: YtripÃÂ atraksi = 175,21ÃÂ +ÃÂ 1,3212ÃÂ XticketÃÂ untukÃÂ stasiunÃÂ Tawang. KorelasiÃÂ antaraÃÂ dayaÃÂ tarikÃÂ dan modaÃÂ transportasi dapat digambarkan dalam persamaan berikut: Ytarikan = 7,3063 + 3271 Xmobil pribadi + 2.464 Xbecak + 2.406 XsepedaÃÂ motorÃÂ +ÃÂ 2.448 Xpick-upÃÂ untukÃÂ stasiun Poncol,ÃÂ dan: YtarikanÃÂ =ÃÂ 4467ÃÂ +ÃÂ 3567 XmobilÃÂ pribadiÃÂ + 2.517 XsepedaÃÂ motor,ÃÂ untukÃÂ stasiunÃÂ Tawang. DapatÃÂ disimpulkanÃÂ bahwaÃÂ ruangÃÂ parkirÃÂ permintaan penumpang masing-masing 1,48 mÃÂ² di stasiun Poncol dan 7,3 mÃÂ² di stasiun Tawang. Perjalanan atraksi perÃÂ tiket di stasiun Poncol 1,0602 dan 1,3212 di stasiun Tawang.Transportasi modus yang dominan digunakan di stasiun Poncol adalah sepeda motor, sedangkan di stasiun Tawang adalah mobil pribadi dan sepeda motor. mobil pribadi sering digunakan karena fasilitas transportasi publik tidak dapat mendukung kebutuhan penumpang kereta. Ada variabel kendaraan pick-up di stasiun PoncolÃÂ PoncolÃÂ karenaÃÂ melayaniÃÂ penumpangÃÂ danÃÂ barang. SRPÃÂ yangÃÂ digunakanÃÂ dalamÃÂ stasiun Poncol untuk penumpang mobil 65 SRP, sepeda motor 282 SRP, pick-up 52 SRP, danÃÂ rodaÃÂ tiga (becak) 64 SRP. SRP yang digunakan dalam stasiun Tawang untuk mobil penumpang 235 SRP, sepeda motor 350 SRP dan roda tiga (becak) 13 SRP Kata kunci: bangkitan perjalanan, kebutuhan parkir, stasiun poncol, stasiun tawang